Secagem do bagaço de cana-de-açúcar e estudo da sua aplicação na remoção de metal pesado - Graebin, Grasielli Orso (2014)
The growth of the sugarcane sector has enhanced the generation of large amounts of waste such as bagasse from sugar cane, a fact that has encouraged the search for new alternatives of it's use. This study aimed to kiln drying and convective dryer bagasse sugarcane and its application in the removal of metal nickel. Fluorescence spectra of X- rays detected the presence of C, O and Si in the biosorbents, and a fibrous structure and apparently fragmented. Thermal analysis has demonstrated that the bagasse has thermal stability up to 80 °C and four stages of weight loss and decomposition of its components. The point of zero charge was 5,38. The ash content of 4,4%. The kiln drying showed the best results obtained by the experimental desing 22 with 4 center points were showed the temperature of 80 °C as more suitable for balancing the end of the drying process of sugar cane bagasse in 140 minutes. In convective drying the best results were at a temperature of 80 °C and the drying air speed of 2,0 m s-1 reaching the equilibrium moisture content (Xe) in 85±8,66 minutes. Page's model represented better the kinetics, with R2 of 0,9948. The coefficient of diffusivity and activation energy for the best drying conditions investigated were 1,4340 x 10-12 m2 s-1 and 0,58 kJ mol-1. In the adsorption process optimized variables by Experimental Desing Full 23 values showed the following: pH = 5,0, temperature = 25°C, agitation rate = 75 rpm and adsorbent mass of 0,1 g. The adsorption kinetics of bagasse presented a qeq of 1,43 ± 0,024 mg g-1 in a time of 120 minutes. The sugar cane bagasse being a low cost, renewable and biodegradable agroindustrial by product, proves to be a potential adsorbent for the removal of nickel metal.